1998
DOI: 10.1097/00000433-199809000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine Derivative Fatalities in South Australia-Is "Ecstasy" the Culprit?

Abstract: The number of deaths due to amphetamine derivatives apparently due to substitution of PMA for MDMA (Ecstasy) have recently increased markedly in Adelaide. Potential users should be warned that PMA has been associated with a much higher rate of lethal complications than other designer drugs, and that no guarantee can be made that tablets sold as Ecstasy are not PMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
79
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 16 publications
0
79
0
1
Order By: Relevance
“…It seems that not all entactogens show similar overdose risks. In fact, although MDA, MDEA and MBDB show acute toxicity levels comparable to MDMA [5] , PMA has been associated with a much higher rate of lethal complications than MDMA [8,9] . Similarly, Carmo et al [10] suggested that 4-MTA in humans has been associated with severe intoxications and several deaths.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that not all entactogens show similar overdose risks. In fact, although MDA, MDEA and MBDB show acute toxicity levels comparable to MDMA [5] , PMA has been associated with a much higher rate of lethal complications than MDMA [8,9] . Similarly, Carmo et al [10] suggested that 4-MTA in humans has been associated with severe intoxications and several deaths.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be a useful way of determining the types of illicit drugs that are being used in a particular community, and to provide information to law enforcement agencies, physicians and users when new drugs with significant side effects such as paramethoxyamphetamine are being introduced, or when purer grades of opiates such as heroin are being sold. Both may be associated with increasing cases of lethal and nonlethal drug toxicity [2,3].…”
mentioning
confidence: 99%
“…The main reported features of these deaths were severe hyperthermia and associated rhabdomyolysis and electrolyte imbalances. Cardiovascular stimulation has also been a reported in cases of PMA intoxication (Byard et al 1998;Felgate et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Para-methoxyamphetamine (PMA) is a substituted amphetamine, which is used as a drug in its own right and has also been sold as "ecstasy" (Cimbura et al 1974;White et al 1997;Byard et al 1998). It has been reported to have a higher rate of lethal complications than other amphetamine derivatives such as 3,4-methylenedioxymethamphetamine (MDMA), having contributed to the deaths of at least 16 people in Australia since late 1994.…”
Section: Introductionmentioning
confidence: 99%